Respuesta :

MsRay

Answer:

(-4, 15)

Step-by-step explanation:

The linear combination method involves combining the system of equations and eliminating one variable to solve for the other.  In the given system, you need to first multiply one of the equations by -1 in order to eliminate the 'y':

-1(3x + y = 3)  or -3x -y = -3

                      + 2x + y = 7

                           -x = 4 or x = -4

Use x = -4 to solve for 'y':

2(-4) + y = 7 or -8 + y = 7

y = 15

Final answer:  (-4, 15)